Management of lighting system in sport center of UiTM main campus, Shah Alam / Sharifah Khuailah Syed Abd Rahim - Syed Abd Rahim, Sharifah Khuailah (2005)
Lighting is one of the most important needs for our activities in every day and night. The topic of "MANAGEMENT OF LIGHTING SYSTEM IN SPORT CENTER OF UiTM MAINCAMPUS, SHAH ALAM" covers the aspect of identifying the types of sports and games, physical requirement needs, exactly illumination of the sport center applied at UiTM Main campus, Shah Alam. Besides, studies concern on lightings' maintenance. The methodologies of studies begin with literature study by Journal, Internet and reference books. Following by interviewing, questionnaires distributed randomly to sport center of UiTM main campus, Shah Alam users. The measure of illumination level reading by lux meter done on four places of case study. The final of research give 25% of random respondent of questionnaire did not satisfy lighting applied at sport center and the main problems of lighting are going from burnout of bulbs or tubes. According to maintenance department, the main factor of lighting was becomes the change of procedure from traditional procedure to contracting procedure. It such the same found by interviewing session. This procedure takes long time to proceed and through many stages. Literature study give comparison lighting applied at UiTM Main campus, Shah Alam and actually illumination. Generally, sport complex UiTM installation on Class II(Intermediate Level Competition) and Class III (Supervised Training). It is because UiTM Sport complex allow public to do competition with paying and depend on type of requirements provide. Strategies and recommendation to maintenance department to do work also suggested.